Diversidade genética de hilídeos do Brasil Central - Oliveira, Hugo Henrique Pádua de (2012)
The anurans are a group of vertebrates with wide geographical distribution that obtained highly evolutionary success, being part of a lineage descendant of early tetrapods, the first vertebrates to conquer the terrestrial environment. Anurans are divided into two suborders: Archaeobatrachia and Neobatrachia. Within the suborder Neobatrachia there is Bufonoidea superfamily, which includes the three families of higher abundance in the neotropical region: Leptodactylidae, Bufonidae and Hylidae. The aim of this study was to analyze cytogenetically species of the family Hylidae of areas of the Cerrado of Goiás, by the technique of conventional cytogenetics and by silver nitrate staining. The metaphases were obtained directly from cell suspensions of spleen, liver and bone marrow. The slides were stained with Giemsa at 8%, to determine the diploid number and chromosome morphology. The species Hypsiboas multifasciatu and Hypsiboas raniceps presented the diploid number 2n=24 and fundamental number FN=48 with positive marks for NORs in chromosomes 8 and 10 respectively. The species Hypsiboas lundii presented diploid number 2n=24 and fundamental number FN=46 due to the presence of acrocentric chromosome in pair 6. The RONs for this species were identified in pericentromeric regions of short arms of chromosome 5 and in telomeric regions of short arms of chromosome 8. Within the genus Hypsiboas, only the species Hypsiboas albopunctatus presented diploid number 2n=22 and fundamental number FN = 44, and by silver staining technique we identified the presence of NORs on the short arms of the telomeric regions of chromosome pair 8. The species Pseudis bolbodactyla presented diploid number 2n=24 and FN=46 evidenced by the acrocentric pair 4. The species Scinax similis and Scinax constrictus showed different karyotypic notations. The species Scinax similis presented karyotype 2n=24 and FN=48 with methacentric and submethacentric chromosomes. We found for the species Scinax constrictus the karyotype notation 2n=22 and FN=44. Differences in the morphology of chromosomes with respect to literature data can be explained by the different criteria used for classification of the chromosomes. The morphology of some of the chromosomes found in this study differs from their representatives described in the literature, and such differences may be explained by adopting different criteria for the classification of chromosomes.